Sensitivity of dose‐estimations for acute acetaminophen overdose in predicting hepatotoxicity risk using the Rumack‐Matthew Nomogram - Summon Chomchai; Pattaraporn Mekavuthikul; Jariya Phuditshinnapatra; Chulathida Chomchai (Wiley, 2022)
Abstract Timely assessment of acetaminophen concentration in overdose situations is not always available in resource‐poor settings. The 150 mg/kg dose‐estimate for acetaminophen is widely considered as criterion for acetaminophen overdose. Its sensitivity and specificity when compared to the 150 mg/L treatment line on the Rumack‐Matthew Nomogram (150‐treatment line) has rarely been evaluated. This is a retrospective chart review of acute acetaminophen overdose patients. We evaluated the sensitivity and specificity of the 150, 200 mg/kg and 8‐ and 10‐g dose‐estimates by plotting the serum acetaminophen levels and using 150‐treatment line on the Nomogram as the treatment cut‐off. A comparison of medical care costs was performed. We enrolled 784 cases for analysis. Median (IQR) age was 23 (20-28) years (81.9% female). There were 545 cases (69.5%) where the estimated ingested acetaminophen dose were ≥150 mg/kg and 406 cases (51.8%) with concentrations ≥150‐treatment line. Hepatotoxicity and acute liver injury (ALI) occurred in 7.3% and 23.9%, respectively. The sensitivity and specificity of 150 mg/kg dose‐estimate for the 150‐treatment line were 92.6% (95% CI 89.6, 94.8) and 55.3% (95% CI 50.3, 60.2). Among patients with dose‐estimate below150 mg/kg, none developed hepatotoxicity and 17 (7.1%) develop ALI. The administration of activated charcoal significantly decreased the risk of being above the 150‐treatment line by half. In resource‐poor setings, the use of 150 mg/kg dose‐estimate as a stand‐alone criteria for initiation of N‐acetylcysteine therapy is satisfactory, especially when combined with decontamination with activated charcoal and follow up of aminotransferase at 24 h.